The Role of ChatGPT in Enhancing Academic Arabic Writing Skills among Students of Arabic Language Education - Rafiatun Najah Qomariah; Awad; Shofil Fikri; Shofia Lazreque (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Salatiga, 2025)
This research examines the role of Artificial Intelligence (AI) ChatGPT in improving the Arabic academic writing skills of students in the Arabic Language Education program at STIT Darul Hijrah Martapura. The goals are to describe (1) how ChatGPT helps students in writing Arabic, (2) the accuracy and relevance of its suggestions in academic writing, and (3) the challenges students face when using ChatGPT for Arabic academic writing. This field study uses a quasi-qualitative method, with data collected through interviews, observation, and documentation. Data analysis is conducted using the Miles and Huberman method. The results of the study showed that 1) 95% of sixth-semester students in the Arabic Language Education Program at STIT Darul Hijrah Martapura used ChatGPT for writing Arabic thesis proposals. ChatGPT helped them generate ideas, translate, and find references. Techniques included asking questions in Arabic, using Indonesian with commands to produce Arabic text, and translating. 2) The accuracy of ChatGPT varied: direct Arabic questions gave more relevant answers, while Indonesian commands were less precise. 3) Challenges included accuracy, cultural context, source verification, and plagiarism concerns, with some students resolving these by cross-checking with dictionaries and online sources.